Bird diversity in a human-modified geothermal landscape of Kamojang, West Java, Indonesia - TEGUH HUSODO; ERRI NOVIAR MEGANTARA; YUDI ROSANDI; INDRI WULANDARI; ZAMZAM I’LANUL ANWAR ATSAURY; SYAHRAS FATHIN AMINUDDIN; SUROSO SUROSO; SYA SYA SHANIDA; YUNUS TOHIR (Society for Indonesian Biodiversity, 2025)
Abstract. Husodo T, Megantara EN, Rosandi Y, Wulandari I, Atsaury ZIA, Aminuddin SF, Suroso, Shanida SS, Tohir Y. 2025. Bird diversity in a human-modified geothermal landscape of Kamojang, West Java, Indonesia. Biodiversitas 26: 5679-5693. A geothermal power plant can significantly impact biodiversity through land-use changes. In general, human-induced habitat modifications alter environmental quality, affecting species composition and ecosystem stability. Due to their sensitivity to habitat changes, birds are bioindicators of ecological health. Therefore, this study aimed to assess trends in bird diversity in the Kamojang Geothermal Power Plant area, West Java, Indonesia, using point count and spotlighting methods. A total of 113 species from 37 families were recorded across various land cover types: natural forests, production forests, horticultural gardens, mixed lands, and replanting areas. Muscicapidae was also the most commonly recorded family. Although species richness has recently decreased due to the conversion of natural forests into horticultural fields, overall bird diversity relatively high. Shannon-Wiener diversity index values ranged from 2.663 to 2.995, indicating a moderate level of diversity. Several species served as bioindicators of habitat quality, including riparian specialists and predatory birds. Additionally, the presence of frugivorous, pollinator, and forest-dwelling birds demonstrates that Kamojang's natural woods continue to support pollination activities, provide suitable habitats, and facilitate seed dispersal, thereby promoting vegetation sustainability. Controlling the expansion of agriculture within the community is crucial to maintaining and enhancing bird diversity in a geothermal environment. Reforestation efforts that account for canopy stratification complexity can effectively restore damaged bird habitats by reintroducing native forest flora, thereby offering cover and helping sustain ecological balance in geothermal landscapes.